Tea polyphenols protect bovine mammary epithelial cells from hydrogen peroxide-induced oxidative damage in vitro by activating NFE2L2/HMOX1 pathways - Ma, Y.F.; Zhao, L.; Coleman, D.N.; Gao, M.; Loor, J.J. (Journal of dairy science, 2019)
Periparturient dairy cows are likely subject to altered intracellular reduction-oxidation (redox) balance due to the high metabolic rates and physiological adaptations occurring around parturition. Such conditions could induce oxidative damage. In nonruminants, it is well established that nuclear factor erythroid 2 like 2 (NFE2L2) is a critical transcription factor for maintaining cellular redox balance by inducing adaptive responses against oxidative stress (OS) that can otherwise lead to uncontrolled inﬂammation. Tea polyphenols (TP), the major polyphenolic constituents of green tea, are potent antioxidants that could exert protective effects on bovine mammary epithelial cells (BMEC) by scavenging free radicals. We used NFE2L2 short interfering RNA (siRNA) to downregulate NFE2L2 expression in cultured BMEC to investigate whether TP could inhibit H2O2-induced OS by activating the NFE2L2/heme oxygenase-1 (HMOX1) pathway. Isolated BMEC were exposed to H2O2 (600 μM) for 6 h to induce OS. Optimal doses of TP (0, 60, 80, and 100 μg/mL) were evaluated by pretreatment of BMEC for 0, 2, 4, 6, 8, 12, and 24 h, followed by a H2O2 (600 μM) challenge for 6 h. The BMEC were transfected with NFE2L2-siRNA for 48 h, pretreated with 100 µg/mL of TP for 12 h, then challenged by 600 μM H2O2 for 6 h. Results revealed that after H2O2 exposure a concentration of TP of 100 μg/mL during a 12-h incubation led to greater cell viability, protein, and mRNA abundance of NFE2L2, and lower intracellular reactive oxygen species (ROS) accumulation. In addition, transfection with NFE2L2-siRNA decreased abundance of NFE2L2 and HMOX1 in spite of exogenous TP supplementation, whereas ROS production was increased in response to exogenous H2O2 (600 μM). Overall, TP had beneficial effects on redox balance in BMEC, slowing down cellular OS-related injury through decreasing the production of ROS and enhancing mechanisms controlled at least in part by the NFE2L2/HMOX1 pathway.